The Impact of Change Management and Culture on the Entrepreneurship Performance in the Industrial Revolution 4.0 in The Bitung City - Trang, Irvan; Tumiwa, Johan (Journal of Ecohumanism, 2024)
The conduct of this research is to analyze and assess and develop a variable and instrument to identify the impact of change management and culture on the entrepreneurship performance in the industrial revolution 4.0 in the Bitung City. Currently, targeted to be achieved in this research is the increase in the entrepreneurship performance in the Bitung City so can increase economic growth in the industrial revolution 4.0 Next, methods used in the approach and research are observation, included identify in this 250 respondents (entrepreneurship) that is there Bitung City, using survey method, share the survey / the questionnaire and provide open questionnaire to get perception accurate data, then process data and evaluate the results to conference and published (international publication). After the results obtained but the results will provide a positive contribution to all stakeholders (Academition, Businessman, Government).